The devil colony : a Sigma Force novel - Rollins, James, 1961- (Rollins, James, 1961- Sigma Force novel., 2011)
After a mountainside massacre yields a grim message, Painter Crowe, director of Sigma Force, must join with Commander Grayson Pierce and an unlikely ally if he is going to get to the root of a conspiracy that stretches back to a lost prehistoric colony in America.